Legal Reconstruction of the Inequality between Medical Service Procedures by Doctors and Cost Control Policies by Hospitals from the Perspective of Justice for Patients Participating in National Health Insurance - Selvi Relita Fitri; Evita Isretno Israhadi (PT. ALHAFI BERKAH INDONESIA, 2025)
This study discusses the challenges and solutions related to the imbalance between hospital cost control and doctor's medical decisions in the National Health Insurance (JKN) system. The main focus of this study is on the protection of patient rights, strengthening the autonomy of the medical profession, and enforcing more transparent regulations in cost management. The analysis highlights the importance of formulating explicit regulations regarding the division of responsibilities between doctors, hospitals, and BPJS, as well as the need for an active role of the government and society in overseeing the implementation of health policies. The study suggests a more equitable and sustainable system update, by paying more attention to patient medical needs and ensuring optimal service quality without being burdened by inappropriate cost policies.